Quantitative metabolomics of a xylose-utilizing Saccharomyces cerevisiae strain expressing the Bacteroides thetaiotaomicron xylose isomerase on glucose and xylose. (1st October 2017) - Mert, M J; Rose, S H; la Grange, D C; Bamba, T; Hasunuma, T; Kondo, A; van Zyl, W H
Abstract: The yeast Saccharomyces cerevisiae cannot utilize xylose, but the introduction of a xylose isomerase that functions well in yeast will help overcome the limitations of the fungal oxido-reductive pathway. In this study, a diploid S. cerevisiae S288c[2n YMX12] strain was constructed expressing the Bacteroides thetaiotaomicron xylA (XI) and the Scheffersomyces stipitis xyl3 (XK) and the changes in the metabolite pools monitored over time. Cultivation on xylose generally resulted in gradual changes in metabolite pool size over time, whereas more dramatic fluctuations were observed with cultivation on glucose due to the diauxic growth pattern. The low G6P and F1, 6P levels observed with cultivation on xylose resulted in the incomplete activation of the Crabtree effect, whereas the high PEP levels is indicative of carbon starvation. The high UDP-d- glucose levels with cultivation on xylose indicated that the carbon was channeled toward biomass production. The adenylate and guanylate energy charges were tightly regulated by the cultures, while the catabolic and anabolic reduction charges fluctuated between metabolic states. This study helped elucidate the metabolite distribution that takes place under Crabtree-positive and Crabtree-negative conditions when cultivating S. cerevisiae on glucose and xylose, respectively.